Renouveler la gestion du risque par l’ouverture à un système de vigilance ? - Catherine Fallon (Éditions en environnement VertigO, 2012)
This contribution proposed by a multidisciplinary group of veterinary and political scientists gives an analysis of the transformations of an epidemiosurveillance system dedicated to animal diseases, when confronted to new emerging threats in the wake of global changes, within the frame of risk management. The research field refers to the emergence of bluetongue virus serotype 8 in 2006 in Belgium. This research is complemented with the results of a recent survey based on Delphi method involving relevant public servants and scientists, which showed that most of the means proposed by the authorities are based on the logic of known risk management. However we can identify attempts for renewal and organisational learning, especially with the proposal of a new vigilance system. This system develops two dimensions (prevention and anticipation of the catastrophe) and tries to accommodate the surveillance system reactivity against uncertain events. Finally the article draws two drivers for change, by admitting the persistence of unavoidable uncertainty and by recognising the importance for opening up expert knowledge.